NILAI INDEKS GLIKEMIK BERBAGAI PRODUK OLAHAN SUKUN (Artocarpus altilis) - Rakhmawati FKR; Rimbawan Rimbawan; Leily Amalia (Jurnal Gizi dan Pangan, 2011)
A new approach based on glycemic index was suggested in choosing foods as a source of carbohydrate. A study on glycemic index of selected Indonesian food has been conducted such as breadfruit which is a source of carbohydrate. The objective of this study was to analyze glycemic index value of breadfruit products such as fried breadfruit, steamed breadfruit, boiled breadfruit, and breadfruit cookies. These processing was choosen based on common method of breadfruit cooking in Indonesia. Breadfruits from Kudus were selected. That breadfruit had processed into four kinds of breadfruit products namely fried breadfruit, steamed breadfruit, boiled breadfruit, and breadfruit cookies. The foods were analyzed the nutrient composition of the four breadfruit products. Six healthy subjects (3 males and 3 females) with BMI between 18.5 and 22.9 kg/m2 were selected. GI value of four breadfruit products determined by standard method (Miller 1996). Measurement of GI was conducted after approval of the Ethics Committee (No. LB.03.04/KE/4914/2010) received. Proximate analysis showed that nutrient contents of the products were as follows : moisture content (wet based, wb) of breadfruit products such as fried breadfruit, steamed breadfruit, boiled breadfruit, and breadfruit cookies were 51.01%, 71.75%, 79.91%, and 4.24% respectively, protein content (dry based, db) were 1.22%, 2.11%, 3.2%, and 3.53% respectively, fat content (db) were 20.07%, 0.61%, 0.73, and 30.12% respectively, carbohydrate by difference content (db) were 73.36%, 90.30%, 90.78%, and 64.37% respectively, and total dietary fiber content (db) were 16.5%, 25.76%, 30.47%, and 4.36% respectively.  The result showed that glycemic index of fried breadfruit, steamed breadfruit, boiled breadfruit, and breadfruit cookies were 82, 89, 85, and 80 respectively. Those four products were classified as high GI category. Statistical analysis showed that treatment did not affect the GI value.